Implementasi Teknik Pengambilan Gambar Oleh Director Of Photography Pada Produksi Video Dokumenter “Dari Rasi Jadi Mimpi: Langkah Menjaga Tradisi” (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2025)
The documentary film “Dari Rasi Jadi Mimpi: Langkah Menjaga Tradisi” was an audiovisual work that portrayed the life and traditions of the Cireundeu Indigenous Community in Cimahi, West Java, with a focus on the consumption of Rasi (cassava rice) as a symbol of food security and cultural identity. The background of this work was based on concerns regarding the gradual marginalization of local traditions due to modernization and changing consumption patterns. This project aimed to document and visually represent the cultural values of the Cireundeu Indigenous Community through an ethical and authentic documentary approach. The production stages consisted of preliminary research, field observation, visual concept development, filming, and post-production. During the production process, the author acted as the Director of Photography (DoP), responsible for visual planning, camera blocking, composition, and lighting strategies adapted to the indigenous environment and technical limitations on site. The results indicated that a visual approach prioritizing authenticity, the use of natural lighting, and visual ethics successfully strengthened the documentary narrative without diminishing its aesthetic value. In conclusion, this documentary functioned not only as an audiovisual work but also as a cultural archive, an educational medium, and a sustainable tool for promoting local culture.